2018
DOI: 10.1093/femspd/fty002
|View full text |Cite
|
Sign up to set email alerts
|

The CRISPR-Cas system in Enterobacteriaceae

Abstract: In nature, microorganisms are constantly exposed to multiple viral infections and thus have developed many strategies to survive phage attack and invasion by foreign DNA. One of such strategies is the clustered regularly interspaced short palindromic repeats (CRISPR)/CRISPR-associated proteins (Cas) bacterial immunological system. This defense mechanism is widespread in prokaryotes including several families such as Enterobacteriaceae. Much knowledge about the CRISPR-Cas system has been generated, including it… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
50
0
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(54 citation statements)
references
References 153 publications
1
50
0
3
Order By: Relevance
“…The results showed that all CRISPR candidates belong to the host species, and they were excluded as possible foreign genetic elements, e.g., from bacteriophages or plasmids. As described by Medina-Aparicio et al 40 , more than 98 (43%) out of 228 complete Enterobacteriaceae genomes analysed lacked CRISPR/Cas systems, including 11 genomes out of all 12 tested from the genus Enterobacter. The results of these analyses and of our research indicate that the distribution of the CRISPR/Cas system in the Enterobacteriaceae family is not regular and rarely found in the genus Enterobacter.…”
Section: Bacteriocin Biosynthesismentioning
confidence: 75%
See 1 more Smart Citation
“…The results showed that all CRISPR candidates belong to the host species, and they were excluded as possible foreign genetic elements, e.g., from bacteriophages or plasmids. As described by Medina-Aparicio et al 40 , more than 98 (43%) out of 228 complete Enterobacteriaceae genomes analysed lacked CRISPR/Cas systems, including 11 genomes out of all 12 tested from the genus Enterobacter. The results of these analyses and of our research indicate that the distribution of the CRISPR/Cas system in the Enterobacteriaceae family is not regular and rarely found in the genus Enterobacter.…”
Section: Bacteriocin Biosynthesismentioning
confidence: 75%
“…Genetic defence mechanism. The use of clustered regularly interspaced short palindromic repeat (CRISPR)/CRISPR-associated proteins (Cas) is one of many bacterial immunological strategies for phage attack or invasion by foreign DNA 40 . This defence mechanism plays a special role, particularly in protecting bacteria against bacteriophage invasion, which is possible during the industrial-scale production of metabolites 31 .…”
Section: Bacteriocin Biosynthesismentioning
confidence: 99%
“…Equivalent arrays show a considerable intraspecific polymorphism in terms of spacer number and sequence. Fundamental knowledge about the CRISPR-Cas mechanism has been generated from the analysis of these two systems in E. coli 10 11 12 13 and related Enterobacteriaceae 14 .…”
Section: Introductionmentioning
confidence: 99%
“…Since there are other effective methods for genome editing in microorganisms such as HR; few studies have been reported on the development of CRISPR-Cas genome editing in various bacteria (i.e., E. coli, Cyanobacteria, Streptomyces, Riemerella anatipestifer, Clostridium, Corynebacterium, Bacillus, Salmonella, Pseudomonas putida, Lactobacillus casei) (63)(64)(65)(66)(67)(68)(69)(70)(71)(72). Identification of strains (73), detection of natural or engineered immunity against mobile genetic elements (74,75), manipulation of microbial consortium (76), and programmable transcriptional regulation (77) are some issues that have been tried to be solved using CRISPR.…”
Section: Bacterial Genome Editing With Crisprmentioning
confidence: 99%